A meta-analysis of the effects of training clinicians in exposure therapy on knowledge, attitudes, intentions, and behavior. (August 2020) - Trivasse, Heidi; Webb, Thomas L.; Waller, Glenn
Abstract: Despite evidence that exposure therapy is an effective way to treat anxiety, many clinicians fail to implement it appropriately. The current review investigated whether training can improve practicing clinicians' beliefs about and implementation of exposure therapy. A systematic search of four databases (PsycINFO, Medline, Scopus, and ProQuest Dissertations and Theses) identified fifteen studies evaluating the impact of training in exposure therapy. A series of meta-analyses revealed that training had large-sized positive effects on clinicians' knowledge of exposure therapy ( d +  = 1.18), attitudes towards exposure therapy ( d +  = 0.84), and self-efficacy associated with delivering exposure therapy ( d +  = 0.72). There were, however, only medium-sized positive effects on clinicians' intentions to use exposure therapy ( d +  = 0.41) and behavior ( d +  = 0.35). These findings suggest that training can provide clinicians with the knowledge and confidence to use exposure therapy, but might not be sufficient to promote changes in practice. Future research should consider incorporating volitional interventions into training (e.g., if-then planning or implementation intentions), in order to bridge this gap. Highlights: Training in exposure therapy has large effects on clinicians' attitudes and knowledge. Such training has smaller effects on their intentions and self-efficacy. Training in exposure therapy has a non-significant impact on clinicians' behaviors.